Contributions of eosinophils to human health and disease - Klion, Amy D. (Annu Rev Pathol, 2020)
The human eosinophil, which typically comprises about 1–5% of all circulating leukocytes, has long been felt to favorably impact innate mucosal immunity but at times has also been incriminated in disease pathophysiology. Research into eosinophil biology, especially with the use of murine models, has uncovered a number of interesting contributions of eosinophils to health and disease. However, it appears that not all eosinophils from all species are created equal. It remains unclear, for example, exactly how having eosinophils benefits the human host when helminth infections in the developed world have become scarce. This review will focus on our current state of knowledge as it relates to human eosinophils from birth to death, from circulation to tissue accumulation, in sickness and in health. When information on aspects of human eosinophil biology are lacking, lessons learned from relevant mouse studies will be discussed, with the understanding that such information may or may not directly apply to human biology and disease. The use of recently approved biologics that selectively target eosinophils, (i.e., precision pharmacology) is now providing the medical community with an exciting opportunity to directly test hypotheses in people by defining the contribution of this cell in eosinophil-associated diseases such as asthma and others. While it is an exciting time to be an “eosinophilosopher”, there remain a number of important challenges and unmet needs in this field that provide opportunities for future studies and advancement as we explore the contributions of this enigmatic cell.